The Implementation Of Training Needs Assessment Among Training Managers In Selected Private Organisations In Malaysia - Yaakub, Ahmad Raji (1996)
This study was designed to determine the extent to which training managers in selected private organisations in Malaysia have adopted the training needs assessment steps or procedures that have been prescribed by experts when conducting training needs assessment for their organisation. It was also designed to identify factors associated with the adoption of the training needs assessment steps or procedures . Data for this study were solicited from 24 respondents through survey using mailed questionnaires . The respondents comprised of training and human resource development managers and executives from various industries , including manufacturing, transport, trading,